Development of Canva-Based Digital Media for Teaching Mathematics: Counting Numbers Up to 10,000 in Grade IV Elementary School - Annisa Salsabila; Annisa Siti Wardah; Salsa Amelia Putri; Tita Mahharani; Alfiana Nurussama; Teten Ginanjar Rahayu (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2026)
This study aims to: a) Test the validity of Canva-based interactive mathematics learning media on whole number materials in elementary school ; and b) Test the practicality level of the learning media according to student responses. This study is a type of Research and Development (R&D) using the ADDIE Development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The Research subjects were fourth-grade elementary school students. The instruments used included validation sheets and practicality questionnaires. The validity test results from material and media experts obtained an average percentage of 87.58%, falling into the